2002
DOI: 10.1128/jvi.76.1.251-258.2002
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Human Fab Fragments against Measles Virus Recovered by Phage Display

Abstract: Five human recombinant Fab fragments (Fabs) specific for measles virus (MV) proteins were isolated from three antibody phage display libraries generated from RNAs derived from bone marrow or splenic lymphocytes from three MV-immune individuals. All Fabs reacted in an enzyme-linked immunosorbent assay with MV antigens. In radioimmunoprecipitation assays two of the Fabs, MV12 and MT14, precipitated an Ϸ80-kDa protein band corresponding to the hemagglutinin (H) protein from MV-infected Vero cell cultures, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Several of these Fabs exhibited neutralizing activity in vitro, but the majority of F-binding Fabs that were isolated did not neutralize virus, consistent with previous reports using phage display technology as a means of sampling specific antiviral human antibody repertoires (2,14,18,86). However, of the 14 F-specific Fabs we identified by ELISA screening, 12 bound hMPV-infected cells, and 4 of these exhibited in vitro neutralizing activity.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Several of these Fabs exhibited neutralizing activity in vitro, but the majority of F-binding Fabs that were isolated did not neutralize virus, consistent with previous reports using phage display technology as a means of sampling specific antiviral human antibody repertoires (2,14,18,86). However, of the 14 F-specific Fabs we identified by ELISA screening, 12 bound hMPV-infected cells, and 4 of these exhibited in vitro neutralizing activity.…”
supporting
confidence: 71%
“…The preparation of combinatorial phage display libraries from variable heavy-and light-chain antibody genes provides an efficient method for the isolation of human antibody Fabs. The construction of antibody libraries on the surface of M13 phage and their application for the generation of human MAbs against numerous viruses have been described in several reports (2,3,9,14,15,18,60,86). Many of these studies reported the isolation of antibodies that neutralize virus in vitro and in vivo.…”
mentioning
confidence: 99%
“…Antigenic site IV must be more distant because the antibody I-44 had lower inhibitory activity. These data show that the receptor binding surface in MVH is a major target for antibody responses neutralizing virus infectivity (21,22). The similarities in blocking receptor binding to MVH among the different monoclonal antibody tested suggest that the shift in receptor usage by MV may not necessarily be driven by specific immune responses.…”
Section: Discussionmentioning
confidence: 84%
“…Mouse monoclonal antibodies binding to MVH (I-12, I-29, I-41, I-44, 16-CD11, and 16-DE6) were prepared from hybridomas (21), and anti-MVH-specific MV4, MV12, and MT14 were human recombinant neutralizing Fabs derived by the phage display method (22).…”
Section: Antibodiesmentioning
confidence: 99%
“…Recently, several recombinant human Fab fragments exhibiting neutralizing activity toward viruses such as human immunodeficiency virus types 1 and 2, Ebola virus, measles virus, Puumala virus, and respiratory syncytial virus were prepared by means of a phage display system (1,3,6,7,28,37,50). Since the amount of surface proteins with neutralization epitopes on viruses is small and the immunogenicity of inner proteins is quite high, it is generally much more difficult to obtain MAbs with neutralizing capacity than nonneutralizing MAbs.…”
Section: Discussionmentioning
confidence: 99%